Fabricating the Absolute Fake America in Contemporary Pop Culture - Kooijman, Jaap (American Studies, 2008)
The pageantry of Oprah Winfrey's talk show, the Coca-Cola empire, Michael Jackson's turn from the King of Pop into an iconic global recluse: American pop culture - Hollywood cinema, television, pop music - dominates the rest of the world through its hegemonic presence. Does that make everyone a hybridized American, or do these elements find mediation within the other cultures that consume them? Fabricating the Absolute Fake applies concepts of postmodern theory - Baudrillard's hyperreality and Eco's "absolute fake," among others - to this globally mediated American pop culture in order to examine both the phenomenon itself and its appropriation in the Netherlands, as evidenced by such diverse cultural icons as the Elvis-inspired crooner Lee Towers, the Moroccan-Dutch rapper Ali B, musical tributes to an assassinated politician, and the Dutch reality soap opera scene. A fascinating exploration of how global cultures struggle to create their own "America" within a post-9/11 media culture, Fabricating the Absolute Fake reflects on what it might mean to truly take part in American pop culture.